Electroacupuncture reduces neuroinflammation and neuronal pyroptosis via downregulating Neat1 in rats after stroke - Bin Chen; Xiaoyong Zhong; Wanqing Lin; Zhaolian Cai; Xiaofang You; Renyu Yu (Stroke and Vascular Neurology)
Background We investigated the potential contribution of the lncRNA Neat1 to the therapeutic efficacy of electroacupuncture (EA) after ischaemic stroke.Methods EA stimulation was used to treat cerebral ischaemia/reperfusion injury (CIRI) in the rat model. Post-therapeutic intervention, infarct volume (IV), brain water content and neurological impairments were assessed. Furthermore, TUNEL and immunofluorescence staining were performed to examine cellular apoptosis, neuronal loss and neuroglial activation. Additionally, Quantitative Real-Time Polymerase Chain Reaction (qRT-PCR), western blotting, ELISA and electron microscopy were employed to assess the NLRC4 inflammasome pathway and neuronal pyroptosis in rats subjected to CIRI.Results Present findings confirmed that EA successfully downregulated Neat1 and IV in response to CIRI. Moreover, the positive impacts of EA on neurobehavioural recovery, suppression of brain damage and reduction in MAP2 degradation were reversed by Neat1 overexpression. Neat1 overexpression also blocked the reduction in NLRC4 activation, including that of components such as NLRC4, Caspase-1 and gasdermin D, as well as the decrease in cellular apoptosis and neuronal pyroptosis induced by EA. Furthermore, Neat1 overexpression counteracted the suppressive effects of EA on proinflammatory microglial polarisation (Iba1+/CD11b+) and increased neurogenesis (Nestin+/Sox2+) in EA-treated rats. Finally, Neat1 overexpression inhibited the ability of EA to lower proinflammatory factors and elevated anti-inflammatory cytokines in the ischaemic striatum.Conclusions These results highlight a novel anti-inflammatory mechanism of EA that involves the lncRNA Neat1/NLRC4 pathway, which regulates the inhibition of neuronal pyroptosis and neuroinflammation. This mechanism may work as an attainable therapeutic objective for EA-induced neuroprotection against ischaemic stroke.